High-performance pyrite nano-catalyst driven photothermal/chemodynamic synergistic therapy for Osteosarcoma - Li, Meirong; Wang, Minghua; Huang, Junfeng; Tang, Shiqi; Yang, Jingyu; Xu, Zhourui; Xu, Gaixia; Chen, Xin; Liu, Jia; Yang, Chengbin (Journal of nanobiotechnology, 2024)
Osteosarcoma (OS) is an aggressive bone tumor with strong invasiveness, rapid metastasis, and dreadful mortality. Chemotherapy is a commonly used approach for OS treatment but is limited by the development of drug resistance and long-term adverse effects. To date, OS still lacks the curative treatment. Herein, we fabricated pyrite-based nanoparticles (FeS 2 @CP NPs) as synergetic therapeutic platform by integrating photothermal therapy (PTT) and chemo-dynamic therapy (CDT) into one system. The synthetic FeS 2 @CP NPs showed superior Fenton reaction catalytic activity. FeS 2 @CP NPs-based CDT efficaciously eradicated the tumor cells by initiating dual-effect of killing of apoptosis and ferroptosis. Furthermore, the generated heat from FeS 2 @CP under near-infrared region II (NIR-II) laser irradiation could not only inhibit tumor’s growth, but also promote tumor cell apoptosis and ferroptosis by accelerating •OH production and GSH depletion. Finally, the photothermal/NIR II-enhanced CDT synergistic therapy showed excellent osteosarcoma treatment effects both in vitro and in vivo with negligible side effects. Overall, this work provided a high-performance and multifunctional Fenton catalyst for osteosarcoma synergistic therapy, which provided a pathway for the clinical application of PTT augmented CDT.